Researching pedagogy in English pre-schools - Siraj-Blatchford, I; Sylva, K (2004)
This article summarizes and reflects on the findings related to pedagogy of two closely associated Department for Education and Skills (DfES) funded research projects: the Effective Provision of Pre-school Education (EPPE) and the Researching Effective Pedagogy in the Early Years (REPEY) projects. 1 The EPPE research project was a five-year longitudinal study funded by the DfES to follow the progress of approximately 3000 children, aged three plus, in 141 pre-schools across England. In addition to the range of quantitative data collected about children, their families and their pre-school centres, 12 effective pre-school settings (selection based on child developmental outcomes) were identified in the EPPE multilevel analysis for intensive, in-depth qualitative case study. The REPEY study provided an opportunity to extend this qualitative analysis further with both naturalistic and systematic observations, interviews and focus group discussions, and allowed the addition of two reception classes (selection based on professional judgement). Together, the studies provide a large-scale, sequential and explanatory mixed method research design investigating pedagogy in 14 Foundation Stage (the key stage for children 3-5) settings. The REPEY research has shown that the most effective pre-school settings (in terms of intellectual, social and dispositional outcomes) achieve a balance between the opportunities provided for children to benefit from teacher-initiated group work, and in the provision of freely chosen yet potentially instructive play activities. The analysis also shows an association between curriculum differentiation and matching in terms of cognitive challenge, and 'sustained shared thinking'. The evidence suggests that the better a setting does on each of these dimensions of pedagogic practice the more effective it will be. The most effective settings also adopt social/behaviour policies that involve staff in supporting children in rationalizing and talking through their conflicts.